2021
DOI: 10.3390/antiox10071079
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sperm Oxidative Stress and Embryo Quality in Advanced Paternal Age Using Idebenone In Vitro—A Proof-of-Concept Study

Abstract: Advanced paternal age is associated with increased sperm reactive oxygen species (ROS) and decreased fertilization and pregnancy rates. Sperm washing during infertility treatment provides an opportunity to reduce high sperm ROS concentrations associated with advanced paternal age through the addition of idebenone. Sperm from men aged >40 years and older CBAF1 mice (12–18 months), were treated with 5 µM and 50 µM of idebenone and intracellular and superoxide ROS concentrations assessed. Following in vitro fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…A limiting factor of current studies is the addition of antioxidants that are not cell permeable [ 132 ], therefore, the positive effects of supplementation seen in these studies maybe more due to extrinsic ROS removal via antioxidant scavenging, as opposed to reducing sperm ROS generation and intrinsic ROS scavenging. Similar to oral antioxidant intake studies, only a few in vitro studies have examined the downstream effects on fertilization, embryo development and live birth reporting favorable outcomes [ 133 , 134 , 135 , 136 , 137 ], which are required in order to provide an evidence base prescribing use of antioxidants in clinical practice. This is important as excessive amounts of antioxidants can have the opposite effect, interfering with physiological ROS concentrations, leading to enhanced ROS generation in mitochondria and lead to further oxidative injury to cells [ 138 , 139 ].…”
Section: Why We Are Still Likely Some Time Away From Semen Ros Measur...mentioning
confidence: 99%
“…A limiting factor of current studies is the addition of antioxidants that are not cell permeable [ 132 ], therefore, the positive effects of supplementation seen in these studies maybe more due to extrinsic ROS removal via antioxidant scavenging, as opposed to reducing sperm ROS generation and intrinsic ROS scavenging. Similar to oral antioxidant intake studies, only a few in vitro studies have examined the downstream effects on fertilization, embryo development and live birth reporting favorable outcomes [ 133 , 134 , 135 , 136 , 137 ], which are required in order to provide an evidence base prescribing use of antioxidants in clinical practice. This is important as excessive amounts of antioxidants can have the opposite effect, interfering with physiological ROS concentrations, leading to enhanced ROS generation in mitochondria and lead to further oxidative injury to cells [ 138 , 139 ].…”
Section: Why We Are Still Likely Some Time Away From Semen Ros Measur...mentioning
confidence: 99%
“…Some studies have found that antioxidants can improve sperm quality in aging males [ 100 , 101 ] and some have found no improvement [ 100 ]. In addition, in vitro studies have found that adding idebenone (a mitochondrial-permeable synthetic benzoquinone that acts as an antioxidant by scavenging free electrons) to the sperm of men over 40 years old can reduce sperm ROS and improve the fertilization rate [ 102 ]. However, the sample size of these studies is small, and the combination of multiple antioxidants is generally used, which cannot effectively prove the specific mechanism of antioxidants.…”
Section: The Application Of Antioxidants In the Treatment Of Male Inf...mentioning
confidence: 99%
“…However, such dysfunction was not reported previously in male LHON patients. In addition, it was observed that idebenone was able to promote the vitality of spermatozoa in animals ( 9 – 11 ). But, such treatment was never used before to treat male infertility due to mtDNA mutation in human.…”
Section: Introductionmentioning
confidence: 99%